2011
DOI: 10.1682/jrrd.2011.01.0013
|View full text |Cite
|
Sign up to set email alerts
|

Repeated concussion among U.S. military personnel during Operation Iraqi Freedom

Abstract: Abstract-Concussions are a predominant injury of the conflicts in Iraq and Afghanistan. The aims of this study were to describe repeated concussive events among U.S. military personnel injured in Operation Iraqi Freedom and examine subsequent healthcare utilization. We reviewed clinical records from the Expeditionary Medical Encounter Database to identify servicemembers with repeat concussions. We abstracted demographic and injury-specific variables, calculated time between events, and identified healthcare ut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…Given the noise hazards prevalent in combat settings, it is critical that deployers obtain a monitoring audiogram before and after deployment. Our findings on causality and types of battle injuries are consistent with other studies [7,[40][41][42]. In general, the most common audiologic symptoms reported in victims of blast are tinnitus and hearing loss, with a significant proportion of patients reporting concomitant tinnitus and hearing loss.…”
Section: Discussionsupporting
confidence: 91%
“…Given the noise hazards prevalent in combat settings, it is critical that deployers obtain a monitoring audiogram before and after deployment. Our findings on causality and types of battle injuries are consistent with other studies [7,[40][41][42]. In general, the most common audiologic symptoms reported in victims of blast are tinnitus and hearing loss, with a significant proportion of patients reporting concomitant tinnitus and hearing loss.…”
Section: Discussionsupporting
confidence: 91%
“…8 A study of deployed U.S. service members found that 87% of second concussions occurred within 30 days of the initial injury, and that severity of the second injury (but not the first) was associated with higher use of mental health and neurological services during the 2 years after injury. 9 This is of concern because early evidence suggests that close temporal proximity of multiple head injuries is associated with poorer recovery. Another study found that Florida National Guard personnel were more likely to receive a diagnosis of probable major depression, anxiety, post-traumatic stress disorder (PTSD), and postconcussion syndrome if they reported sustaining multiple MTBIs, as opposed to a single injury.…”
Section: Introductionmentioning
confidence: 99%
“…According to the Department of Veterans Affairs (VA) and the Department of Defense, the criteria for an mTBI are-A physiological disruption of brain function as a result of a traumatic event as manifested by at least one of the following: alteration of mental state, loss of consciousness (LOC), loss of memory or focal neurological deficit, that may or may not be transient; but where the severity of the injury does not exceed the following: post-traumatic amnesia (PTA) for greater than 24 hours, after the first 30 minutes Glasgow Coma Score (GCS) [13][14][15], and loss of consciousness is less than 30 minutes. [5] While penetrating TBI events are apparent immediately, mTBIs often go unrecognized [6].…”
Section: Introductionmentioning
confidence: 99%
“…The accurate proportion of mTBI among injured servicemembers is in all probability higher than reported because closed TBIs are not diagnosed in a prompt manner [7]. The incidence of TBI among Iraq and Afghanistan Veterans is approximately 15 to 20 percent, with research demonstrating that mTBI is the most common form of TBI among this Veteran cohort [2,[8][9][10][11][12][13][14]. Because of multiple deployments and exposures to blasts, some of these Veterans have sustained repeated mTBIs [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation